'Abd al-Lạtīf al-Bagdadi's philosophical journey : from Aristotle's Metaphysics to the 'Metaphysical Science' - Bonadeo, Cecilia Martini. (Islamic Philosophy, Theology and Science. Texts and Studies, 2013)
Although the philosopher ʿAbd al-Laṭīf al-Baġdādī (1162 -1231) received an extensive education in the thought of Avicenna, he still journeyed long in search of true philosophy. It was in Cairo that he finally discovered a model of philosophical metaphysics rooted in Greek thought as set out in Kindian and Farabian writings. This volume is devoted to the study of Aristotle's Metaphysics and other Greek metaphysical writing gathered together by this Muslim philosopher to form a 'Metaphysical Science' in his Book of the Science of Metaphysics ( Kitāb fī ʿilm mā baʿd al-ṭabīʿa ).